2020
DOI: 10.29052/ijehsr.v8.i3.2020.139-144
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in the population of Karachi, Pakistan; A cross-sectional study

Abstract: Background: Vitamin D deficiency affects over one billion people globally, which results in the progression of severe health consequences and chronic diseases. Literature indicates high rates of vitamin D deficiency in the Pakistani population. Thereby, this current study was aimed to determine the status of vitamin D deficiency in the population of Karachi. Methodology: This descriptive cross-sectional study was conducted during January to December 2017 at the Dadabhoy Institute of Higher Education (DIHE). A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Low vitamin D is reported in Asian nations, but the problem is not limited to a single country or continent and has been reported globally. 2 Its role in skeletal health has been recognized for several years. 3 Earlier, Holvik et al 4 conducted a vitamin D prevalence study and reported low vitamin D in Sri Lankan immigrants.…”
Section: Introductionmentioning
confidence: 99%
“…Low vitamin D is reported in Asian nations, but the problem is not limited to a single country or continent and has been reported globally. 2 Its role in skeletal health has been recognized for several years. 3 Earlier, Holvik et al 4 conducted a vitamin D prevalence study and reported low vitamin D in Sri Lankan immigrants.…”
Section: Introductionmentioning
confidence: 99%